Gaya Hidup, Kualitas Produk dan Word of Mouth Terhadap Keputusan Pembelian, Keputusan Pembelian Sepatu Converse di Kota Semarang - Kenang Gusti Haryanto; Ajeng Aquinia (IPM2KPE, 2023)
This research aims to find out how lifestyle, product quality, and word of mouth influence consumer purchasing decisions. The research method used was quantitative which was carried out in Semarang. This research used a purposive sampling technique with 100 respondents. The data analysis techniques used are validity testing with KMO (Kaiser Mayer Olkin) and factor loading (component matrix), reliability testing with Cronbach alpha and multiple regression analysis. The research results show that lifestyle and product quality influence purchasing decisions and word of mouth does not influence purchasing decisions. The conclusion is that the higher the consumer's lifestyle when shopping, the greater the purchasing decision, the better the quality of the product will attract more consumers to buy the product and this means that the purchasing decision made by consumers of Converse shoes is not due to word of mouth factors experienced and felt by consumers. Keywords: Lifestyle, Product Quality, Purchasing Decisions, Word Of Mouth